Tumorigenicity of the miR-17-92 cluster distilled - van Haaften, Gijs (Cold Spring Harbor Laboratory Press, 2010)
The miR-17-92 gene cluster, with its six different mature microRNAs (miRNAs), has an established oncogenic function. However, the oncogenic contribution of each individual miRNA in the cluster has not been assigned. Two studies published in the December 15, 2009, issue of Genes & Development by Mu and colleagues (pp. 2806–2811) and Olive and colleagues (pp. 2839–2849) dissected the miR-17-92 cluster to its individual miRNA components and identified their relative contributions to oncogenic transformation in mouse model systems.